Special education teacher resilience: A qualitative case study at special elementary school in Semarang Indonesia - Fitriyati; Jatie Kusmiati Kusna Pudjibudojo; Aniva Kartika (Universitas Sarjanawiyata Tamansiswa, 2025)
Teacher resilience plays a crucial role in sustaining special education, particularly amid high teacher turnover in special schools. This study aims to explore the meanings and dynamics that sustain the resilience of two senior teachers at a Special Needs Elementary School in Semarang, Indonesia, who have remained in the profession for over 12 years despite systemic limitations and emotional challenges. Grounded in an interpretivist–constructivist paradigm, this qualitative case study employed semi-structured in-depth interviews, non-participant classroom observations, and interviews with parents or guardians as source triangulation. Data were analyzed thematically with a constructivist lens to reveal the meanings of experience, capturing the embedded meanings in teachers' resilience withinspecial education settings. The analysis revealed six core themes: (a) transformation of motivation from economic needs to professional dedication, (b) enhanced self-worth through students' achievements,(c) development of a growth mindset, (d) emotional closeness with students, (e) sublimation of personal struggles into professional strength, and (f) collegial and organizational support. Furthermore,the research findings reveal a new contextual dimension, namely professional persistence, which represents teachers' determination to continue teaching despite facing structural and emotional obstacles in the local context of special schools in Semarang. This dimension emerges as a unique form of resilience, reflecting not only the ability to persist but also a conscious choice to continue professional commitment despite less than supportive working conditionssustainably. Thus, professional persistence broadens the understanding of teacher resilience as a contextual response rooted in their values, meanings, and professional identities.